2010
DOI: 10.1111/j.1365-2702.2009.02989.x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in nurses – the relationship between social capital in hospitals and emotional exhaustion

Abstract: Efforts to create a good working atmosphere with readiness to provide mutual support and the pursuit of joint values in a hospital, the reduction of workload and increased decision latitude may prevent the development of emotional exhaustion in nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
159
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(181 citation statements)
references
References 53 publications
9
159
1
9
Order By: Relevance
“…On the contrary, another study reported that gender is not an important predictor of burnout (24). In the present study, no significant correlation was found between the age of the subjects and different subscales of burnout, which are in line with the results of two other studies (25,26). Results of the present study also showed that the relationship between job experience and burnout is only meaningful in the emotional subscale meaning that as job experience increases, burnout decreases.…”
Section: Discussionsupporting
confidence: 81%
“…On the contrary, another study reported that gender is not an important predictor of burnout (24). In the present study, no significant correlation was found between the age of the subjects and different subscales of burnout, which are in line with the results of two other studies (25,26). Results of the present study also showed that the relationship between job experience and burnout is only meaningful in the emotional subscale meaning that as job experience increases, burnout decreases.…”
Section: Discussionsupporting
confidence: 81%
“…Older therapists remember sayings such as "empathy defeats therapy" (49), but such attitudes have fallen away as psychologists increasingly have placed a premium on empathic care during the therapeutic process. In a related vein, within the field of nursing, the importance of empathy and compassion for patients is emphasized so unrelentingly that it would be reasonable to explore the possibility of a causal relationship between the unilateral focus on caring and the severe issue of burnout among nurses (50). Health care workers are not taught about the potential hazards of excessive or misplaced empathy; consequently, a gradual dehumanization process unfolds (51).…”
Section: Discussionmentioning
confidence: 99%
“…Burnout has been linked to higher rates of absenteeism than the general population [20], and to increased nurse turnover [21] and decreased job satisfaction [22]. Leiter and Maslach and Kowalski et al found that heavy perceived nurse workloads were associated with one component of burnout, emotional exhaustion [23,24]. Without adequate resources and supports to meet workload demands, nurses grow dissatisfied and emotionally exhausted; they burn out and leave-sometimes leaving the profession altogether [21].…”
Section: Workload Outcomesmentioning
confidence: 99%